Rural tourism - the chance of the 21th century - Tomic, Slavica (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
.Global changes in the tourist market are characterized by an increasing representation of tourist forms differentiating from those for which the system 3S is valid (sun, sea, sand). The contemporary trend of moving from the concept of mass tourism to the individual forms of tourism opens to rural tourism the position in the world market of the 21th century. Rural tourism has no characteristics of massiveness and it is compatible with the aspects of sustainable tourism.